Anemia and ferropenia in pregnancy: from evidence to practice (Portuguese Journal of Family Medicine and General Practice, 2024)
Screening for anemia in pregnancy is routine clinical practice, given its prevalence and impact on maternal and fetal health. Iron deficiency is the main cause of anemia, however, it can occur in the absence of anemia and must be treated. Nevertheless, the measurement of ferritin in the absence of anemia is not consensual and, according to some authors, may lead to a lack of adequate treatment for pregnant women with iron deficiency, without anemia. A commonly adopted strategy that can minimize this risk, involves universal iron supplementation in pregnancy, which, in turn, also deserves reflection and scrutiny, since inadequate iron supplementation in pregnancy can also produce deleterious maternal and fetal effects. The purpose of this article is to reflect on clinical practice in this context, where guidelines can be ambiguous or even contradictory.
Keywords: Anemia; Iron deficiency; Pregnancy